(untitled) (Journal of Nobel Medical College, 2021)
The world’s health in 2020 was in the grip of the COVID-19 pandemic and its adverse consequences and is still continuing in 2021. Most countries have been locked down or going through different forms of lockdown to prevent the transmission of the infectious virus SARS-CoV-2. To date, there is no specific treatment or vaccination preventive measures. World Health Organization has approved few vaccines for emergency use. Still, the emergence of mutations within SARS-CoV has put forward challenges for vaccine developers. Whether infectious or non-infectious, all diseases have an inflammatory aspect to alarm the body system along with an anti-inflammatory counterbalance mechanism to minimize harmful effects whether through immune modulation or antioxidant reserves. An approach to counteract the novel disease, COVID19, was also sought in enhancing the anti-inflammatory aspect, at the level of prevention and at the level of treatment. One of the methodologies was the recommendation of micronutrient Vitamin D whose immune-modulatory role has been well appreciated in many disease conditions. This short review aims to explore the relationship between vitamin D status through susceptibility and clinical outcomes of COVID-19.